Mechanical Property of Lateral Piles for Pile Composite Foundation Loaded by Model Test - Chen-xi Feng; Hang Yuan; De-quan Zhou; Peng Du; Chuang-ye Wang; Qiu-ling Yang; Fei Pang; Min Jing; Hui-xian Yu (Advances in Civil Engineering)
Under vertical load, the composite foundation may be damaged due to insufficient lateral restraint capacity. If the lateral restraint pile is added to the edge of the composite foundation, the lateral stability can be effectively enhanced. This new reinforcement scheme is called a combined composite foundation. For the combined composite foundation, the lateral restraint piles will bear a certain force when the composite foundation is loaded, and the force may cause the piles horizontal displacement, instability, or even failure. After preload on the composite foundation, the mechanical behavior of lateral restraint piles will be more sophisticated. To study the mechanical behavior of lateral restraint piles under such condition, a laboratory model test was conducted. The results are suggested as follows: Axial force distribution curves tend to be “S” shape with two peak values at the upper and lower parts, respectively. The negative axial force is distributed at the upper part, and the positive axial force is distributed at the lower part. The bending moment and lateral soil pressure distribution of piles appear with the regularity of “increase-decrease” along the depth. Such a phenomenon is associated with the expansion of a potential slip surface. In accordance with the relative location of the potential slide surface and the piles, the lateral restraint piles can fall into three sections. Different sections get different stresses. The reinforcement scopes have an impact on the stress of different lateral restraint piles. With the increase of the reinforcement scope, the axial force, soil pressure, and bending moment show the regularity of increase. The values of axial force, the lateral soil pressure, and the bending moment increase with load growth and become stable when the load is larger than 60 kN. This is associated with the piles in the composite foundation, which verifies the reinforcement effect to prevent the soil slide and the foundation deformation.